Chapter La morte del re, le ragioni del diritto e l'etica dei mercanti in una causa fiorentina del Quattrocento - TANZINI, LORENZO (Reti Medievali E-Book, 2021)
The essay analyzes a judicial case of the Mercanzia court in the early Quattrocento Florence, which involved the execution of an insurance deed by the merchant and poet Cino Rinuccini concerning the date of the death of Ladislaus king of Naples in 1414. The case, considering the relevance of the actor and the subject of the insurance agreement, allows us to study the discussion on the legal and ethical value of such deeds. The Appendix provides the edition of a legal consilium devoted to the case, in which a distinguished commission of lawyers discusses the problem according to the interpretation of the ius commune.